Determination of the thyroid volume by ultrasonography – comparison with surgical facts - Hussy, Elvira; Voth, E.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: Objective of this prospective study was to find out, if especially the volume of large nodular goitres can be determined accurately by using ultrasonography and the ellipsoid model. Methods: 100 patients with different thyroid disorders, who all underwent a thyroid resection, were examined by a single experienced investigator. The preoperative thyroid volume was determined by ultrasonography and correlated to the sum of surgically removed and postoperative thyroid volume determined by ultrasound. Results: Patients included had thyroid volumes between 12 and 450 ml (mean value 89 ml). Within the whole study group, coefficients of correlation and variation were r = 0.90 and CV = 0.29, respectively. The mean difference between the thyroid volume determined preoperatively by ultrasonography and the sum of surgically removed and postoperative thyroid volume was 3 ± 27 ml or 13 ± 38%. Excluding patients with retrosternal goitres or cysts with a diameter >2 cm, the correlation coefficient increased to r = 0.95 (CV = 0,21 ) and mean differences decreased to 2 ± 20 ml and 9 ± 30%. Further subdivision according to thyroid volume (≤50 ml, ≤ 100 ml, >100 ml) revealed no significant influence of thyroid volume on the accuracy of ultrasound volume determination. Subdividing the study collective according thyroid disorders, relevant deviations of preoperative sonographic thyroid volume from the sum of surgically removed and postoperative thyroid volume were observed in case of retrosternal goitre (19 ± 62%), cystic degeneration (41 ± 52%) and Graves’ disease (23 ± 29%). Conclusion: These results show, that even large suprasternal goitres >100 ml can be sufficiently determined by ultrasound by an experienced examiner.
Keywords: Thyroid gland; goitre; real time ultrasonography; thyroid volume; ellipsoid model; thyroidectomie